HPV Testing from Dried Urine Spots as a Tool for Cervical Cancer Screening in Low-Income Countries. (9th June 2015) - Frati, Elena Rosanna; Martinelli, Marianna; Fasoli, Ester; Colzani, Daniela; Bianchi, Silvia; Binda, Sandro; Olivani, Pierfranco; Tanzi, Elisabetta
Abstract : Nowadays, several screening strategies are available to prevent cervical cancer, but inadequate resources, sociocultural barriers, and sampling issues impede their success in low-income countries. To overcome these issues, this study aimed to evaluate the performance of human papillomavirus (HPV) testing from dried urine spots (DUS). Eighty-eight urine samples (including 56 HPV DNA positive specimens) were spotted on filter paper, dried, and stored in paper-bags. HPV DNA was detected from the DUS after 1 week and 4 weeks of storage using a polymerase chain reaction (PCR) assay. The sensitivity, specificity, and concordance of the DUS-based HPV test were evaluated by comparing the results with those of HPV testing on fresh urine samples as the gold standard. The sensitivity of the test was 98.21% (95% CI: 90.56–99.68) for DUS stored for 1 week and 96.42% (95% CI: 87.88–99.01) for DUS stored for 4 weeks. The specificity was 100% (95% CI: 89.28–100) at both time points. The concordance between DUS and fresh urine HPV testing was "almost perfect" using the κ statistic. These preliminary data suggest that a DUS-based assay could bypass sociocultural barriers and sampling issues and therefore could be a suitable, effective tool for epidemiological surveillance and screening programs, especially in low-income countries.